KRITIK MATAN HADIS - Muhsin, Masrukhin (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2017)
The criticism of  hadith  practiced by muhaddithin and recognized by Muslim scholars is by using muqaranah and mu'aradah methods  proved to be more accurate, precise and comprehensive, rather than the method used by Western scholars using the common link method. The methods of muqaranah and mu'aradah essentially compare the existing concepts in one hadith with the existing concepts on the Qur'an, Hadith Mutawatir,  reason / logic and others, while the common link method compares only word per word. The same words are considered valid while different words are considered weak hadith. Keywords: Muqaranah, Mu‘aradah, Common link.